Rotinas do tráfico: estratégias, custos e lucratividade na carreira escravista portuguesa (1750-1770) - ELLI, Moreno (2021)
Over four centuries, almost 12 million of enslaved Africans were shipped out to Americas, to toil on the crops work and/or others crafts as well. The operationalization of such trade was sponsored by several business groups, which, operating in different places of the Atlantic basin, should manage at his in best the opportunities that a slave voyage could provide: selling goods, collecting freights and shipping the human cargo to the western Atlantic shore. In this manner, the Portuguese slave trade stood out as one of the most enduring and dynamic route. Whether in Angola, or above the equator, on the Slave Coast, such traders dealt with several local agents, engaging in relationships that were part of the itinerary, paying duties or services, that were part of mercantile calculation. This research aims to assess the different costs that affect the profitability of the business, either in the outfitting, the goods that made up the cargoes and the customs that were part of the daily routine of those undertaking this trade.